A Nanoparticle-Based Biosensor Combined With Multiple Cross Displacement Amplification for the Rapid and Visual Diagnosis of Neisseria gonorrhoeae in Clinical Application - Chen, Xu; Huang, Liming; Zhou, Qingxue; Tan, Yan; Tan, Xuhong; Dong, Shilei (Frontiers in Microbiology, 2021)
Gonorrhea is a sexually transmitted disease caused by the host-adapted human pathogen Neisseria gonorrhoeae, the morbidity is sustained increase and pose a major public health concern, especially in resource scarcity regions worldwide. Devising a rapid, visual, sensitive, specific, cost-saving and simple assay for detection of N. gonorrhoeae is critical for promptly treatment and prevention of further transmission. Here, we firstly report a novel assay, multiple cross displacement amplification combined with gold nanoparticle-based lateral flow biosensor (MCDA-LFB), which was applied for rapid and visual identification of N. gonorrhoeae in clinical samples. The results showed that the set of MCDA primers were successfully devised according to N. gonorrhoeae-specific gene orf1. The optimal conditions of N. gonorrhoeae-MCDA-LFB can be carried out at 67℃ for 30 min. The whole process, including genomic DNA preparation (~10 min), MCDA amplification (30 min), and LFB reading (~2 min), could be completed within 50 min. The limited of detection (LoD) of N. gonorrhoeae- MCDA-LFB assay was 20 copies per test. The specificity of this assay was one hundred percent, and has no cross-reactions to other pathogens were observed. These results indicated that N. gonorrhoeae-MCDA-LFB is a rapid, specific, visual, cost-saving, and easy-to-operation assay for diagnosis of N. gonorrhoeae, which has great potential to exploit a point-of-care (POC) testing for clinical application, especially in resource shortage regions worldwide.